2008
DOI: 10.1111/j.1439-0310.2008.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mating Increases Fecundity, Fertility and Relative Clutch Mass in the Female Leopard Gecko (Eublepharis macularius)

Abstract: Females across many taxa may mate with several males or mate more than once with the same male within one reproductive event. Although many researchers have discussed the effects of multiple mating on reproductive success of females, few studies have attempted to disentangle whether the reproductive success of females differs with respect to whether females mate with multiple males or mate more than once with one male. In this study, we hypothesized that female leopard geckos (Eublepharis macularius) increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 77 publications
(175 reference statements)
2
13
0
Order By: Relevance
“…For instance, mating with multiple males has been shown to be beneficial to females in echinoderms (Evans and Marshall 2005), insects (Tregenza and Wedell 1998;Fedorka and Mousseau 2002;Dunn et al 2005), fishes (Evans and Magurran 2000) and reptiles (LaDage et al 2008), but it can also be associated with a reduction of the female's reproductive output, as reported for many insect species (e.g., Orsetti and Rutowski 2003;Bybee et al 2005;Ronkainen et al 2010). At the same time, several studies found no effect of polyandry on female fecundity in insects (e.g., Baker et al 2001;Schwartz and Peterson 2006;House et al 2009).…”
Section: Introductionmentioning
confidence: 93%
“…For instance, mating with multiple males has been shown to be beneficial to females in echinoderms (Evans and Marshall 2005), insects (Tregenza and Wedell 1998;Fedorka and Mousseau 2002;Dunn et al 2005), fishes (Evans and Magurran 2000) and reptiles (LaDage et al 2008), but it can also be associated with a reduction of the female's reproductive output, as reported for many insect species (e.g., Orsetti and Rutowski 2003;Bybee et al 2005;Ronkainen et al 2010). At the same time, several studies found no effect of polyandry on female fecundity in insects (e.g., Baker et al 2001;Schwartz and Peterson 2006;House et al 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Whether females chose to mate with more than one male may have been related to other traits such as age, size, or parental investment (LaDage et al. ) that could have resulted in spurious effects of paternity status on survival to metamorphosis. Although this possibility for maternal effects cannot be ruled out, we believe it to be unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Some species exhibit oneegg (e.g., Anolis (Smith, Sinelnik, Fawcett, & Jones, 1973)) or two-egg clutches (e.g., many geckos including Eublepharis (LaDage, Gutzke, Simmons, & Ferkin, 2008)) produced repeatedly over the course of a breeding season, whereas other species produce clutches averaging approximately 20-30 eggs produced once per breeding season (e.g., Phrynosoma (Ballinger, 1974;Endriss, Hellgren, Fox, & Moody, 2007)). Some species exhibit oneegg (e.g., Anolis (Smith, Sinelnik, Fawcett, & Jones, 1973)) or two-egg clutches (e.g., many geckos including Eublepharis (LaDage, Gutzke, Simmons, & Ferkin, 2008)) produced repeatedly over the course of a breeding season, whereas other species produce clutches averaging approximately 20-30 eggs produced once per breeding season (e.g., Phrynosoma (Ballinger, 1974;Endriss, Hellgren, Fox, & Moody, 2007)).…”
Section: Evolutionary Considerationsmentioning
confidence: 99%
“…This species is native to southwestern Asia, although most if not all studies on its reproduction have occurred in laboratories using animals from captive-bred stock. Adult females lay two-egg clutches (or, rarely, one-egg clutches) repeatedly across the breeding season (Rhen et al, 2000;LaDage et al, 2008). Adult females lay two-egg clutches (or, rarely, one-egg clutches) repeatedly across the breeding season (Rhen et al, 2000;LaDage et al, 2008).…”
Section: Cordylidaementioning
confidence: 99%
See 1 more Smart Citation